A literature review of the research on ferroelectric polymers. Issue 1 (May 2021) - Kumar, Vivek; Babu, T; Tiwari, Balgovind
Abstract: In this work, the research and development of ferroelectric polymers has been reviewed. The main focus is on properties of different types of ferroelectric polymers. Ferroelectrics of ceramic and thin film nature, are widely known for their use in several electronic devices. But the existence of ferroelectricity in polymers has made the ferroelectric polymers to be used in different electrical applications such as sensors, actuators, etc. The main theme of this paper is to report only the existing literature on ferroelectric-polymeric materials.